Handbook of design and analysis of experiments - Dean, Angela; Morris, Max 1950-; Stufken, John; Bingham, Derek (Chapman & Hall/CRC handbooks of modern statistical methods, 2015)
Handbook of Design and Analysis of Experiments provides a detailed overview of the tools required for the optimal design of experiments and their analyses. The handbook gives a unified treatment of a wide range of topics, covering the latest developments.This carefully edited collection of 25 chapters in seven sections synthesizes the state of the art in the theory and applications of designed experiments and their analyses. Written by leading researchers in the field, the chapters offer a balanced blend of methodology and applications.The first section presents a historical look at experiment.